1999
DOI: 10.1016/s0022-2275(20)33418-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors and age-related decline in apolipoprotein A-I expression

Abstract: Apolipoprotein (apo)A-I alone or as a component of high density lipoprotein particles has antiatherogenic properties. The age-dependent decline in abundance of this protein may underlie the higher risk for developing occlusive coronary artery disease (CAD) in older individuals. Similar to humans, expression of rat apoA-I also declines with age. Results in rats showed that levels of serum apoA-I protein, hepatic mRNA, and transcription of the gene were decreased to 39%, 18%, and 38%, respectively, in 180-day-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Apolipoprotein A-1 (APOA1) is the major protein component of high density lipoprotein (HDL) in plasma. The expression level of APOA1 in blood has been reported to decrease with age [52,53]. In this study, APOA1 was detected only in the youngest infant (0.75 years old), which is consistent with the previous research [52,53].…”
Section: Protein Quantitation Using Exponentially Modified Protein Abundance Indexsupporting
confidence: 92%
“…Apolipoprotein A-1 (APOA1) is the major protein component of high density lipoprotein (HDL) in plasma. The expression level of APOA1 in blood has been reported to decrease with age [52,53]. In this study, APOA1 was detected only in the youngest infant (0.75 years old), which is consistent with the previous research [52,53].…”
Section: Protein Quantitation Using Exponentially Modified Protein Abundance Indexsupporting
confidence: 92%
“…Effects of COUP-TF Proteins on Apo A1. COUP-TF family proteins, by displacing HNF-family proteins from their proximal promoter sites, are major regulators of apo A1 transcription in vivo and in vitro ( , ). To determine if changes in COUP levels mediated the effects of TO901317, total COUP-TF was first assayed in Hep3B cells by Western blotting in the presence and absence of the ligand, using an antibody detecting both COUP-TF1 and COUP-TF2.…”
Section: Resultsmentioning
confidence: 99%
“…HNF proteins react as homodimers with direct repeats (DRs) based on a regulatory sequence (AGGTCA) separated by a single nucleotide. A second family of transcription factors, chicken ovalbumin upstream promoter transcription factors (COUP-TFs), inhibits apo A1 transcription competitively ( , ). Two closely related proteins, COUP-TFI and COUP-TFII, are expressed in liver cells.…”
mentioning
confidence: 99%
“…Many but not all epidemiological studies have indicated a closer association of HDL apolipoprotein A-I with heart disease risk than with HDL-C. [4][5][6][7][8] ApoA-II associated with HDL2 does not seem to have a similar protective effect. 4,[7][8][9] In patients with diabetes, glycosylation of HDL may result in a functionally abnormal and atherogenic apolipoprotein A-I particle. [10][11][12][13] Traditionally, protein expression levels in plasma samples have been compared using one-dimensional or two-dimensional (1D and 2D) gel electrophoresis.…”
Section: Introductionmentioning
confidence: 93%
“…Plasma high-density lipoprotein cholesterol (HDL-C) levels are inversely correlated with risk for atherosclerosis. The mechanism(s) for this association may involve reverse transport of cholesterol. Many but not all epidemiological studies have indicated a closer association of HDL apolipoprotein A-I with heart disease risk than with HDL-C. ApoA-II associated with HDL 2 does not seem to have a similar protective effect. , In patients with diabetes, glycosylation of HDL may result in a functionally abnormal and atherogenic apolipoprotein A-I particle. …”
Section: Introductionmentioning
confidence: 99%